2020
DOI: 10.1051/0004-6361/201937153
|View full text |Cite
|
Sign up to set email alerts
|

Implications of three-dimensional chemical transport in hot Jupiter atmospheres: Results from a consistently coupled chemistry-radiation-hydrodynamics model

Abstract: We present results from a set of simulations using a fully coupled three-dimensional (3D) chemistry-radiationhydrodynamics model and investigate the effect of transport of chemical species by the large-scale atmospheric flow in hot Jupiter atmospheres. We couple a flexible chemical kinetics scheme to the Met Office Unified Model which enables the study of the interaction of chemistry, radiative transfer and fluid dynamics. We use a newly-released "reduced" chemical network comprising 30 chemical species that h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(139 citation statements)
references
References 100 publications
(255 reference statements)
7
132
0
Order By: Relevance
“…Disequilibrium processes, such as vertical or horizontal mixing could also play an important role in distributing metal oxide/hydrides on the day-side of KELT-9 b (Kitzmann et al 2018;Komacek et al 2019;Drummond et al 2020). To investigate those processes, one should compare the timescales of the creation and destruction reactions with the timescales of dynamical processes.…”
Section: Discussionmentioning
confidence: 99%
“…Disequilibrium processes, such as vertical or horizontal mixing could also play an important role in distributing metal oxide/hydrides on the day-side of KELT-9 b (Kitzmann et al 2018;Komacek et al 2019;Drummond et al 2020). To investigate those processes, one should compare the timescales of the creation and destruction reactions with the timescales of dynamical processes.…”
Section: Discussionmentioning
confidence: 99%
“…5. Chemical disequilibrium between CH4 and CO was suggested as a possible culprit for HD 189733b and HD 209458b (Knutson et al 2012;Zellem et al 2014), but recent GCM experiments rule out this explanation (Steinrueck et al 2019;Drummond et al 2018aDrummond et al , 2020. More likely is that the discrepancies result from clouds and/or hazes, although this possibility remains to be quantified in detail.…”
Section: Gcm Experiments and Comparison To Observationsmentioning
confidence: 99%
“…As a consequence the final atmospheric abundances are determined by the vertical mixing strength on the dayside atmosphere and the pressure and temperature at the quench point, where the vertical mixing timescale equals the chemical timescale. Drummond et al (2018a) and Drummond et al (2020) additionally showed that the meridional circulation could also mix the chemical composition latitudinally, meaning that the 3D nature of the atmospheric mixing by the circulation should not be ignored. Finally, differences between chemical schemes (e.g.…”
Section: Chemistrymentioning
confidence: 99%
“…When the chemical conversion timescales is close to or longer than dynamical timescales, the potential correlation between horizontal distribution of chemical species (therefore their radiative feedback) and large-scale dynamics may play a similar role as a dynamically active tracer, contributing to the heating/cooling rates that shape the circulation. Such radiative feedback by chemical quenching on the general circulation has been investigated for hot Jupiters (e.g., Steinrueck et al 2019;Drummond et al 2020), and will be an interesting topic in future studies for BDs and directly imaged EGPs.…”
Section: Unresolved Issues and Outlookmentioning
confidence: 99%